Bahasa Humor dalam Tradisi Guyon Jawa: Kajian Etnolinguistik tentang Identitas dan Solidaritas Sosial - Handa, Esa Futuh; Azizi, Mohammad Sofwan; Baehaqie, Imam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines Javanese humor through an ethnolinguistic approach to understand the relationship between humorous forms, cultural values, and communicative practices within Javanese society. It combines ethnolinguistic and sociolinguistic perspectives and employs a descriptive qualitative method. Data were collected from humorous interactions in traditional market transactions, interviews, and documentation of Jula Juli performances and digital content. The findings reveal that Javanese humor serves to maintain social harmony, strengthen interpersonal relationships, and convey criticism in subtle ways. The use of wordplay, semantic shifts, and distinctive humorous patterns demonstrates both linguistic creativity and social sensitivity. In everyday contexts, humor functions as a medium that reinforces solidarity, while in performances and digital spaces, it affirms cultural identity and reflects the community’s adaptation to changing times. This study highlights that Javanese humor is an essential part of intangible cultural heritage, embodying the values of rukun, tepa selira, and nrima.